Conceptual blending and the fulfilment quotation in Matthew 12:17–19 - Mushayabasa, Godwin (HTS teologiese studies, 2022)
This article revisits the age-old question of the sources of Matthew’s fulfilment quotations (FQs), specifically Matthew 12:17–19. Despite the presence of numerous studies on this topic, this study was necessitated by the need to incorporate insights from conceptual blending in order to explore how the source(s) of the quote was used. In addition, this study was also done with a possible view to complementing the textual criticism of Old Testament (OT) texts which happen to be quoted or referred to in the New Testament (NT). The study dwells on intertestamental and cognitive linguistics studies. It was found that Matthew may have composed the Matthew 12:17–19 FQ, and possibly the other FQs as well, aided by conceptual integration mechanisms.Contribution: The source of Matthew’s quotation need not wholly be found in a specific historical text but should also include the cognitive operations in the author’s mind and intentions, thus resulting in a text that might not have existed in the form represented in the quotation.